2020
DOI: 10.1101/2020.06.15.151720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cannabidiol Interactions with Voltage-Gated Sodium Channels

Abstract: Voltage-gated sodium channels are targets for a range of pharmaceutical drugs developed for treatment of neurological diseases. Cannabidiol (CBD), the non-psychoactive compound isolated from cannabis plants, was recently approved for treatment of two types of epilepsy associated with sodium channel mutations. This study used high resolution X-ray crystallography to demonstrate the detailed nature of the interactions between CBD and the NavMs voltage-gated sodium channel, showing CBD binds at a novel site at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…5C. The similarities in the general effects of CBG and CBD on Nav gating and kinetics prompt us to suggest that CBG could bind at a similar location within the Nav fenestrationcentral cavity site that CBD binds (31). Additionally, the steepness of the concentration-response curves along with the physicochemical properties of CBG could also suggest a possible modulation of the membrane elasticity, which could contribute to the hyperpolarization of the inactivation curve at higher than physiologically conceivable concentrations (e.g., >15 µM), without altering voltage-dependence of activation.…”
Section: Cbg -Possible Mechanism Of Nav Inhibitionmentioning
confidence: 99%
See 3 more Smart Citations
“…5C. The similarities in the general effects of CBG and CBD on Nav gating and kinetics prompt us to suggest that CBG could bind at a similar location within the Nav fenestrationcentral cavity site that CBD binds (31). Additionally, the steepness of the concentration-response curves along with the physicochemical properties of CBG could also suggest a possible modulation of the membrane elasticity, which could contribute to the hyperpolarization of the inactivation curve at higher than physiologically conceivable concentrations (e.g., >15 µM), without altering voltage-dependence of activation.…”
Section: Cbg -Possible Mechanism Of Nav Inhibitionmentioning
confidence: 99%
“…It is previously shown that CBD has no molecular selectivity among the channels in the Nav superfamily (31)(32)(33). The equipotent inhibition of the Navs has been in part ascribed to the binding of CBD at the central cavity-fenestration interface within the lipid phase of the membrane.…”
Section: Cbg Is a State-dependent Inhibitor Of Sodium Currentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sodium current passing through voltage-gated sodium channels (Nav) initiates action potentials in excitable cells. Nav channels are hetero-multimeric proteins composed of large ion conducting α-subunits and smaller auxiliary β-subunits (Isom et al, 1992;Catterall, 2012;Calhoun and Isom, 2014;Ghovanloo et al, 2016bGhovanloo et al, , 2018Ghovanloo and Ruben, 2020;Sait et al, 2020). The SCN5A gene encodes Nav1.5, which is the predominantly expressed Nav in the myocardium (Jiang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%